1996
DOI: 10.1016/s1010-7940(96)80311-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thoracic epidural analgesia on pulmonary function after coronary artery bypass surgery

Abstract: Thoracic epidural analgesia yields a slight, but significant, improvement in pulmonary function, most likely due to a more profound postoperative analgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
1
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(45 citation statements)
references
References 15 publications
3
34
1
7
Order By: Relevance
“…4,5,7,14 However, patients with epidurals in these studies, were extubated three to five hours postoperatively, while tracheal extubation took place within minutes of the conclusion of the operation in our study, the majority of the time while patients were in the operating room. The details of our ultra-fast track program have been described elsewhere.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…4,5,7,14 However, patients with epidurals in these studies, were extubated three to five hours postoperatively, while tracheal extubation took place within minutes of the conclusion of the operation in our study, the majority of the time while patients were in the operating room. The details of our ultra-fast track program have been described elsewhere.…”
Section: Discussionmentioning
confidence: 56%
“…However, there have been conflicting reports regarding the effects of TEA on postoperative pulmonary function and atelectasis. [3][4][5][6] A recent meta-analysis by Liu et al 12 with a combined total of 1,178 patients, found that TEA decreased the incidence of pulmonary complications. in the present study, TEA was associated with a significant improvement in pulmonary function during the first two postoperative days, using FEV 1 as a surrogate for pulmonary function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Post-operative pain may cause hypo-ventilation and insufficient cough, leading to retention of airway secretions and aggravation of the impaired lung function. 6 General Anaesthesia is the most commonly used anaesthetic technique and is considered the gold standard for CABG, performed either on-pump or off-pump. Within the last few years, however, high thoracic epidural analgesia (TEA) as an adjunct to General Anaesthesia has become more prevalent and has been shown to have potentially benefited in patients with coronary artery disease.…”
Section: Evaluation Of Pulmonary Function After Offpump Coronary Artementioning
confidence: 99%